Employee Engagement And Leader-Member Exchange Form Organizational Commitment And Organizational Citizenship Behavior. Can It Be Achieved For Employees Who Work While Studying? - Hayati, Diana; Rifani, Ahmad (Journal of Ecohumanism, 2025)
This study aims to explore the relationship between employee engagement (EE) and leader-member exchange (LMX) in shaping organizational Commitment (OC) and organizational citizenship behavior (OCB) among employees who work while studying. Data was collected from 291 respondents who had worked for at least 1 year in various sectors. Using the Structural Equation Modeling approach, the results of the study showed that employees who had a high level of engagement and good relationships with leaders tended to show a higher commitment to the organization and a higher OCB. Based on the results of the study, five direct influences produce positive and significant numbers, namely EE against OC, EE against OCB, LMX against OC, LMX against OCB and OC against OCB. The indirect influence of EE on OCB through OC also produces a positive and significant, meaning that OC plays a role in mediating the influence of EE on OCB. The indirect impact of LMX variables on OCB through OC is also positive and significant, meaning that OC mediates the influence of LMX on OCB.